Understanding the Role of Social Networks in Education for Sustainable Development and Climate Change Education - Kolleck, N.; Jörgens, H. (59th Annual Convention of the International Studies Association “Power of Rules and Rule of Power”, 2018)
While there is little doubt that social networks are essential for processes of implementing social innovations such as Education for Sustainable Development (ESD) or Climate Change Education (CCE), scholars have neglected to analyze these processes with techniques of Social Network Analysis. In this article, we contribute to closing this research gap by exploring the realization of ESD and CCE in community education at the national, regional and global level. We compare the way the UN Decade of ESD is put into practice through networks in five different German municipalities with the way CCE is negotiated and implemented within and through the global conferences surrounding the UN Framework Convention on Climate Change (UNFCCC). We argue that the role of social networks is particularly strong in policy areas like ESD and CCE which are best characterized as multi-level and multi-actor governance. Based on data derived from standardized surveys and from Twitter we analyze the complex interactions of public and private actors at different levels of governance, focusing especially on the position of international secretariats therein. We find, amongst others, that the implementation of ESD and CCE depends in part on actors that had not been assumed to be influential at the outset.